“Art Should Always Ennoble”: Emma Griesbach and Art Appreciation in the Women's Page of The Farmers’ Sun, 1917-1922 - Halpern, Monda; Halpern, Sonia (Ontario History, 2011)
Between 1917 and 1922, Emma Griesbach edited the women’s page of The Farmers’ Sun. The newspaper became the official organ of the United Farmers of Ontario (UFO), which swept to provincial victory in 1919. The UFO recruited rural female support through the United Farm Women of Ontario (UFWO) in which Griesbach was a leading activist. Through her women’s page in The Farmers’ Sun, Greisbach espoused the tenets of the UFO and UFWO to her female readers in an effort to make them more politically aware, and thus elevate the quality of their lives. Notably, she encouraged them to better their lot through their own cultural development. She wrote numerous columns seeking to expose them to the “highbrow” world of art. In doing so, Emma Griesbach shifts our attention to women’s connection with art in the neglected context of rural life.